1991
DOI: 10.1136/jmg.28.12.884
|View full text |Cite
|
Sign up to set email alerts
|

Two sisters with mental retardation, cataract, ataxia, progressive hearing loss, and polyneuropathy.

Abstract: Two sisters are described with a disorder characterised by mental retardation, congenital cataract, progressive spinocerebellar ataxia, sensorineural deafness, and signs of peripheral neuropathy. Progressive hearing loss, ataxia, and polyneuropathy became evident in the third decade. The differential diagnosis of this syndrome is discussed including the syndromes described by Berman et a) and Koletzko et a].Ataxic syndromes combined with mental retardation have often been described'2 and sometimes these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The hearing loss associated with the present syndrome links this case with a familial syndrome with ataxia, hearing loss, and mental retardation described by several authors ( Berman et al, 1973 ; Koletzko et al, 1987 ; Begeer et al, 1991 ; Koskinen et al, 1994 ) , where hearing loss had been confirmed by audiometry‐ and/or brainstem‐evoked auditory potentials, although sural nerves have not been studied in these cases, and in HMSN‐LOM where there is hearing loss and progressive loss of nerve fibers in the sural nerve ( Kalaydjieva et al, 1996 ; Baethmann et al, 1998 ; King et al, 1999 ). The neuropathologic correlation to the hearing deficit in our patient may possibly, but cannot unequivocally, be attributed to some shrunken or hypereosinophilic neurons in the vestibulo‐cochlear nuclei, because other brainstem nuclei of cranial nerves were likewise affected.…”
Section: Discussionsupporting
confidence: 64%
“…The hearing loss associated with the present syndrome links this case with a familial syndrome with ataxia, hearing loss, and mental retardation described by several authors ( Berman et al, 1973 ; Koletzko et al, 1987 ; Begeer et al, 1991 ; Koskinen et al, 1994 ) , where hearing loss had been confirmed by audiometry‐ and/or brainstem‐evoked auditory potentials, although sural nerves have not been studied in these cases, and in HMSN‐LOM where there is hearing loss and progressive loss of nerve fibers in the sural nerve ( Kalaydjieva et al, 1996 ; Baethmann et al, 1998 ; King et al, 1999 ). The neuropathologic correlation to the hearing deficit in our patient may possibly, but cannot unequivocally, be attributed to some shrunken or hypereosinophilic neurons in the vestibulo‐cochlear nuclei, because other brainstem nuclei of cranial nerves were likewise affected.…”
Section: Discussionsupporting
confidence: 64%
“…Cataracts and hearing loss can occur as major findings in multiple disorders caused by teratogenic exposures, chromosomal and metabolic abnormalities, as well as disorders with single gene inheritance [Bader et al, 1985; Begeer et al, 1991; Guala et al, 1992; Nadol and Burgess, 1982; Nucci and Mets, 1990]. These include disorders such as Stickler syndrome, rhizomelic chondrodysplasia punctata, mannosidosis (alpha B), Zellweger syndrome, and fetal rubella syndrome; however, these patients lacked other key manifestations of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, MSS is clinically heterogeneous 18 with a marked variation in severity and the occasional presence of the following features: peripheral neuropathy, 19 -24 seizures, 10,25 microcephaly, optic atrophy, 26 hearing loss, 27,28 acute rhabdomyolysis 23 and various patterns on magnetic resonance imaging (MRI) such as cerebral atrophy, diffuse reduction of cerebral white matter, 25,29 agenesis of the corpus callosum, 30 abnormal pituitary gland, 25 cyst of the posterior fossa and brainstem atrophy. Moreover, cataract, initially described as congenital, was also found with early childhood onset and rapid progression.…”
Section: Introductionmentioning
confidence: 99%